Mechanistic study of surface functionalization of enzyme lysozyme synthesized Ag and Au nanoparticles using surface enhanced raman spectroscopy - Das, Raja; Jagannathan, Ramya; Sharan, Chandrashekhar; Kumar, Umesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
The fate of bioactivity of biomolecules such as enzymes, proteins, and even drug molecules is greatly affected by the conformational changes in the proximity of the solid surfaces. This interaction is the key to the potential of their further applications as biosensors, in drug delivery, etc. With increasing interest in the biofunctionalization of noble metal nanoparticles for various applications, it is important to precisely investigate the functional groups responsible for binding with the nanoparticle surfaces and probable structural changes in the structure of the biomolecules as both are key factors affecting the bioactivity of these molecules once they are tagged onto the nanoparticle surfaces. However, it is not an easy task to probe these properties, especially for bigger Molecules such as enzymes and proteins. Surface-enhanced Raman spectroscopy (SERS) has been used extensively in the detection of biomolecules and study of their conformation on noble metal surfaces since its discovery because of its high sensitivity. This technique is capable of detecting changes in the secondary structure and the effects of surrounding environment on the biomolecule in the proximity of nanoscopic rough metal surfaces. In this study, we have used this technique to precisely determine the functional groups responsible in the Surface capping of Ag and Au nanoparticles synthesized by the hen egg derived enzyme lysozyme. The sharp and intense Stokes Raman shift peaks observed around 704, 866, 1519, and 1598 cm(-1), in the case of Ag nanoparticles, which are assigned to tryptophan, tyrosine, phenylalanine, and histidine residues, clearly indicate the involvement of these residues for surface passivation of the Ag nanoparticle surface. The Ag-N peak situated around 236 cm(-1) was also seen in the spectra, showing that probably the amine group of lysozyme is responsible in binding to the Ag nanoparticle surface. Similarly, in the case of Au nanoparticles, we observed sharp and intense peaks around 1583, 1545, and 1584 cm(-1) which were assigned to above-mentioned amino acid residues, indicating that a similar mechanism is also responsible for the binding of lysozyme molecules at the Au nanoparticle surface. In both cases peaks for the amide III band (C-N-H) around 1250 cm(-1) were also observed.